“What It Means To Be a Woman:” Ambivalent Sexism in Female College Students’ Experiences and Attitudes. - Fields, Alice; Swan, Suzanne; Kloos, Bret (Sex Roles, 2010)
This study used content analysis to examine if themes related to ambivalent sexism (Glick and Fiske ) emerged when female students wrote an essay answering the question “What does it mean to be a woman?” and examined the relationship between Ambivalent Sexism Inventory (ASI) scores (Glick and Fiske ) and content analysis. Participants were 78 female undergraduate students in the Southeastern U.S. Findings revealed themes related to ambivalent sexism were present in 99% of essays, indicating that ambivalent sexism is highly relevant to women’s gendered experiences. Furthermore participants’ ASI scores were positively correlated with a sexism score created from coded essay content. The discussion addresses theoretical and contextual implications of the findings.